Anti-colonial thought and global social theory - Patel, Sujata (Frontiers in Sociology, 2023)
From the late 1980s onward, global social theory has been introduced to a new perspective variously called indigeneity, endogeneity, Orientalism, Eurocentrism, post-colonial, decolonial, and Southern sociology/social sciences. This study argues that the above-mentioned trends should be collectively termed anti-colonial social theory as all of these explore the relationship between colonialism and knowledge production. The study divides the growth of anti-colonial social theory in terms of two phases and relates it to changing geopolitics of the 20th century. It argues that these distinct trends manifest a united stance in its ontological-epistemic articulation. It also argues that anti-colonial social theory can play a relevant role in a knowledge system divided through colonial/imperial relationships, given its theorization on the same.